PENGARUH INTERACTION ACTIVITIES, ENGAGING CONTENT, DAN ENDORSEMENT DI INSTAGRAM DALAM MENINGKATKAN BRAND AWARENESS CARL & CLAIRE DI JABODETABEK - Ciptadi, Anastasia Melia; wijaya, Shierli (Jurnal Nusa Manajemen, 2025)
With the increasingly intense business competition on social media, marketing strategies have become essential to attract potential customers. The right strategy not only enhances brand awareness but also supports long-term business growth. This study aims to analyze the influence of interaction activities, engaging content, and endorsements on the brand awareness of Carl & Claire, a premium perfume specialist in Indonesia, focusing on the Jabodetabek area. This research employs a descriptive quantitative method with purposive sampling, involving 160 respondents who are Instagram users. The data collected were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that interaction activities, engaging content, and endorsements significantly influence the improvement of Carl & Claire's brand awareness. These findings are expected to serve as a basis for the company in designing more effective social media marketing strategies.